2020
DOI: 10.1111/aor.13873
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracorporeal membrane oxygenation in critically Ill COVID‐19 patients and predictors of mortality

Abstract: Background The role of extracorporeal membrane oxygenation (ECMO) in the management of critically ill COVID‐19 patients remains unclear. Our study aims to analyze the outcomes and risk factors from patients treated with ECMO. Methods and Results This retrospective, single‐center study includes 17 COVID‐19 patients treated with ECMO. Univariate and multivariate parametric survival regression identified predictors of survival. Nine patients (53%) were successfully weaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 39 publications
1
59
1
Order By: Relevance
“…Acute myocardial injury in the absence of macroscopic coronary artery disease is suspected to occur in up to 10% of patients especially in the critically ill 15‐18 . In a recent retrospective analysis, Zayat et al found that, among others, increased levels of amino‐terminal pro‐brain natriuretic peptide (NT‐pro‐BNP) predict worse survival in COVID‐19 patients on extracorporeal life support 19 . While 11% of our participants reported that they employed also veno‐arterial ECLS for COVID‐19, only 3% of participants specified that arterial cannulation was required because of acute heart or circulatory failure, in one case caused by fulminant pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial injury in the absence of macroscopic coronary artery disease is suspected to occur in up to 10% of patients especially in the critically ill 15‐18 . In a recent retrospective analysis, Zayat et al found that, among others, increased levels of amino‐terminal pro‐brain natriuretic peptide (NT‐pro‐BNP) predict worse survival in COVID‐19 patients on extracorporeal life support 19 . While 11% of our participants reported that they employed also veno‐arterial ECLS for COVID‐19, only 3% of participants specified that arterial cannulation was required because of acute heart or circulatory failure, in one case caused by fulminant pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our ECMO administration approaches, including configuration and the applied techniques, were recently published [11]. We used iLA activve ® Pumpe (XENIOS, Heilbronn, Germany) and Cardiohelp HLS Systems Version 7.0 (Maquet Cardiopulmonary GmbH, Rastatt, Germany) ECMO pumps.…”
Section: Ecmo Settingsmentioning
confidence: 99%
“…Our experience as a COVID-19 referral center is consistent with what has been described in the literature. COVID-19 warrants long ECMO runtime and, if necessary, several oxygenator changes or even recannulations, because these factors seem to not be associated with poor survival [ 91 , 184 , 227 , 231 ].…”
Section: Special Considerationmentioning
confidence: 99%